Identifying opportunities for bottom-up industrial symbiosis - Evaluating a method of data gathering for information exchange platforms - Axelsson, Lovisa; Blomé, Simon (My University, 2017)
Industrial symbiosis is a way to reduce the demand on the earth’s resources by enabling the use of waste from one industry as raw material in another. Different interventions are needed to facilitate industrial symbiosis and one of these are information exchange platforms. There is no existing platform for promoting regional symbiosis in the Gothenburg area. For such a platform to be able to facilitate industrial symbiosis it has to contain relevant data. The purpose of this thesis is to investigate what data that should be included in such a platform. We will also evaluate a method of how the data should be collected and organised to make it comprehensible. This will be explored in the thesis by answering the following research question: How can data be collected and organised for an information exchange platform to support bottom-up industrial symbiosis? This project maps the closed loop supply chains of beer and mushroom in the Gothenburg region and quantifies the recurring waste streams related to those industries to identify symbioses opportunities with other industries. 18 interviews were conducted with companies in the two supply chains as well as other relevant stakeholders to gather data and understand the current system. Furthermore, the approach of this thesis is evaluated in order to develop a method that could be used for an information exchange platform to support industrial symbiosis. Five steps were identified; (i) collect data, (ii) structure data, (iii) identify opportunities, (iv) investigate feasibility of opportunities, (v) facilitate the opportunities. Opportunities for symbiosis in the case studies were identified both within and outside of the investigated system. The most promising opportunities in the beer chain is to use the spent grain and yeast as animal feed. For the mushroom chain the most feasible opportunities are to recirculate spent mushroom compost as soil amendment and mushroom leftovers as animal feed or further refine it to additional products. Some of the stakeholders have symbiotic relationships in place for those resources and these could be mimicked by the ones not already engaged. This thesis is conducted at Challenge Lab, at Chalmers University of Technology, which aims to guide master students to become change agents and take on complex societal sustainability challenges. The thesis process in Challenge Lab utilises backcasting to find research questions and to find strategies for a sustainable future.
Keywords: Annan naturvetenskap; Hållbar utveckling; Other Natural Sciences; Sustainable Development